Pancasila: Looking For the Ideal Format of State Philosophy Embodiment - Indah Cahyani; Gatoet Poernomo; Helmy Boemiya (Jurnal Dinamika Hukum, 2022)
Looking for the ideal format of the philosophy of Pancasila embodiment is a scientific article aimed at solving legal problems related to the position of Pancasila in legal construction in Indonesia. It happens because of the unconsistency in the Indonesian legal system. The purpose of this study is to find the most appropriate embodiment of the Pancasila philosophy in the Indonesian legal system. It is an effort in order that the Indonesian legal system has “tools” to ensure or “force” the consistency within Indonesian legal system itself. This study uses a conceptual approach and a legal history approach. The researcher finds that the use of Pancasila philosophy in the construction of the Indonesian legal system is inconsistent. The results of the study conclude that Pancasila needs to be embodied, in order that the law in Indonesia can be more consistent with the goals of the philosophy of the state. The results of this paper recommend that Pancasila, as a philosophy, is the domain of the institution holding the people's sovereignty; that is the House of Representatives and is not an executive domain with the HIP Bill or with the executive-made BPIP institution.Keywords: State Philosophy; Pancasila; Embodiment.